The hybrid designer/end-user: Revealing paradoxes in co-design. (September 2015) - Taffe, Simone
Abstract : Although the benefit of including end-users in design is well documented, little research exists on how participation in design influences end-users. Co-design promotes designing with rather than for end-users. When designing with end-users, designers suppose that the identity and role of designers and end-users remains discrete and stable, however this paper challenges this assumption. This paper discusses a graphic design study where participants co-designed sustainable cleaning information, arguing that end-user participation in graphic design is complex, revealing paradoxes for designers engaging with end-users. In the study the client-perceived end-users reacted negatively to co-designing outcomes targeted for themselves; they joined with the designers forming a hybrid designer/end-user, together proposing outcomes for alternative imagined end-users. Highlights: Co-design workshops in graphic design reveal complex end-user engagement. End-users resist designing outcomes for themselves. End-users talk and behave like designers. End-users propose design solutions for more relevant set of end-users rather than themselves. Designer and end-user participants merge into a hybrid designer/end-user.